A 3-D model for quantification of fatigue weak-link density and strength distribution in an A713 cast aluminum alloy. (March 2017) - Yang, Lin; Cai, Pei; Xu, Zhiqiang; Jin, Yan; Liang, Chunyong; Yin, Fuxing; Zhai, Tongguang
Highlights: A 3-D model was developed to quantify fatigue weak-links in Al cast alloys. The simulated cracking rate at pores was a Weibull function of the cyclic stress. The simulated and experimental weak-link strength distributions were consistent. The model was validated by the experimental results in A713 Al alloys. The minimum critical pore size for crack initiation was 11 μm at 100%σy . Abstract: A quantitative model which took into account the 3-D effects of pores on the local stress/strain fields was developed to quantify the fatigue weak-link density and strength distribution in an A713 Al alloy. In the model, a digital pore structure was first constructed using single-sized pores (15 μm in diameter) that had a total volume fraction same as that of the pores measured experimentally in the alloy. In the surface randomly selected by cross-sectioning through the simulated pore structure, the stress and strain fields around each pore in the surface were quantified using a 3-D finite element model under an applied cyclic stress, and the fatigue crack incubation life at the pore was estimated with a micro-scale Manson-Coffin equation. The quantified rate of fatigue crack initiation at these pores was found to be a Weibull function of the applied stress, which was consistent with the experimental result measured in the alloy. The density and strength distribution of fatigue weak-links could then be derived and used to evaluate the fatigue crack initiation properties of the alloy. By matching to the experimentally measured fatigue weak-links, the minimum critical pore size for fatigue crack initiation was determined to be 11 μm in diameter at the cyclic maximum stress of 100% yield strength of the alloy.